(untitled) (Research, Society and Development, 2020)
This study analyzes the execution of public projects formalized as agreements in Plataforma + Brasil, within the scope of a Federal Institution of Higher Education, located in the Northeast region of the country. From an exploratory / descriptive, bibliographic / documentary analysis and the analysis of 18 projects developed, it was found that, in relation to the time variable, 72.21% of the agreements take up to four months from the proposition to the celebration phase. In addition, 66.66% take up to two months from the celebration to the execution phase. Regarding the additive term variable, it was found that the majority occurred due to non-compliance with the execution schedule. In relation to the variable adjustment of the work plan, a large part had the object of relocating items, in view of the price gap and the adequacy of the project to unforeseen needs. As for the application income, the uses were made due to insufficient financial resources to attend emergency cases. Regarding the fulfillment of goals, 35.29% of the agreements concluded that presented accountability had partial fulfillment of goals. Finally, the results show that delays in the physical and disbursement schedule generate constant needs for the readjustment of projects and are the main factors that affect the execution of the agreements.